Intergroup Relationships, Discrimination, and Prejudice in Germany and Europe - Huth-Stöckle, Nora; Justus Liebig University Giessen (My University, 2024)
This dissertation investigates perceived group threats and their role in intergroup relations between native majorities and immigrant minorities in Germany and Europe. The first study investigates how economic downturns and perceptions thereof affect the perception of immigrants as a threat to the national economy. The second study examines whether pandemic-related challenges and concerns are associated with group-level threat perceptions and anti-immigrant prejudice. The third study investigates the relationship between empathy and prejudice towards refugees. This study further examines whether group threats moderate the relationship between empathy and prejudice. The fourth study investigates the impact of German natives’ social distance towards immigrant groups on these groups’ social distance toward Germans, and to what extent perceived discrimination mediates this association.
Keywords: ddc:300